Effects of Organizational Climate on Work Efficiency Through Work Life Quality of Employees in Suranaree Idustrial Zone - Tanimkarn, Patima; Pukahuta, Penporn (Academic Journal of Management Technology, 2022)
The objective of the present study was to investigate the effects of organizational climate on work efficiency through work life quality of employees in Suranaree Industrial Zone. The data were collected through a questionnaire administered to 224 employees and analyzed using descriptive statistics and structural equation modeling technique. The results indicated that organizational climate and work life quality had significant effects on staff’s working efficiency. Moreover, the study revealed that the relationship between organizational climate employees’ work efficiency was fully mediated by employees’ work life quality. Therefore, to increase organizational performance, it is highly recommended that manager promote the quality of work life approach and develop staff’s abilities and skills by providing them with training and workshop sessions. To promote organizational climate, the manager should encourage team spirit, camaraderie, and generosity, and provide suggestions to company’s members, create employees’ participation, and establish a suitable moral system to increase work efficiency.